Inner egg shell membrane based bio-compatible capacitive and piezoelectric function dominant self-powered pressure sensor array for smart electronic applications. Issue 49 (7th August 2020) - Saqib, Qazi Muhammad; Khan, Muhammad Umair; Bae, Jinho
Abstract : Inner egg shell membrane based bio-compatible capacitive and self-powered piezoelectric pressure sensor array is proposed, with capacitive sensitivity of 37.54 ± 1.488 MPa −1 (0 ≤ P ≤ 0.05 MPa) and piezoelectric pressure sensitivity of 16.93 V MPa −1 (0 ≤ P ≤ 0.098 MPa). Abstract : Flexible pressure sensors play a key role as an interface between the mechanical movements and electrical stimuli in smart skins, soft robotics, and health monitoring systems. However, conventional pressure sensors face several challenges in terms of their bio-compatibility, higher cost, and complicated fabrication process. This paper demonstrates a novel 5 × 5 bio-compatible capacitive and self-powered piezoelectric pressure sensor array using natural inner egg shell membrane (IESM). The proposed sensor array is supported by two different sensing modes, which are capacitive and piezoelectric function dominant self-powered mode. The capacitive mode can detect both static and dynamic pressures and the piezoelectric function dominant self-powered mode can be adopted to detect the dynamic pressure applied on the device. The fabricated device with a sensing area of 4 mm 2 offered the sensitivity of 37.54 ± 1.488 MPa −1 in the capacitive pressure sensing range from 0 to 0.05 MPa. The device showed the response ( T res ) and recovery time ( T rec ) of 60 ms and 45 ms, respectively. The device achieves the sensitivity of 16.93 V MPa −1 from the sensing range of 0 to 0.098 MPa in the self-powered pressure sensing. These results depict that the proposed pressure sensor array will ensure a promising role in green, wearable, and soft electronic applications.